Quantum metrology with single spins in diamond under ambient conditions. Issue 3 (11th October 2017) - Chen, Ming; Meng, Chao; Zhang, Qi; Duan, Changkui; Shi, Fazhan; Du, Jiangfeng
Abstract: The detection of single quantum systems can reveal information that would be averaged out in traditional techniques based on ensemble measurements. The nitrogen-vacancy (NV) centers in diamond have shown brilliant prospects of performance as quantum bits and atomic sensors under ambient conditions, such as ultra-long coherence time, high fidelity control and readout of the spin state. In particular, the sensitivity of the NV center spin levels to external environmental changes makes it a versatile detector capable of measuring various physical quantities, such as temperature, strain, electric fields and magnetic fields. In this paper, we review recent progress in NV-based quantum metrology, and speculate on its future.